Modelling Positive Behaviour: A Vital Strategy in Instilling Positive Discipline Among Secondary School Learners - Lwazi Sibanda; Joyce Mathwasa (RIRAI Publisher, 2020)
This qualitative study, guided by interpretive paradigm, explored how secondary schools use modelling positive behaviour strategy to instil positive discipline among learners in Bulawayo Metropolitan Province, Zimbabwe. The study was enthused by the abolition of corporal punishment, exclusion due to delinquent behaviour and adoption of positive, inclusive discipline strategies to maintain order in schools. A case study design purposively sampled four schools in which four school heads, twenty members of the disciplinary committee, four school counsellors, two education officers, four School Development Committee chairpersons and forty prefects participated. Data collected through focus group interviews, semi-structured interviews and document analysis were thematically analysed. The results indicated that secondary schools adopted the modelling positive behaviour strategy to instil positive discipline among learners. New staff members’ orientation focused on conduct, modelling of positive behaviour whenever teachers, learners and parents interact as they perform various activities in the school environment. The study also established that prefects as role models were afforded opportunity to lead assembly sessions. The study concluded that in spite of a few cases of misconduct, it is evident that modelling positive behaviour strategy produced affirmative outcomes in schools understudy. The study recommends further research that explores other strategies that could be adopted by schools to maintain positive discipline particularly in rural schools.